High-zinc material bottom blowing smelting process

CN122918346APending Publication Date: 2026-10-16HUNAN HUAXIN RAREANDPRECIOUS METALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610944199.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

1.本发明的工艺通过调控入炉炉料的钙硅比(CaO/SiO2质量比)和铁硅比(FeO/SiO2质量比),配合富氧底吹强化熔炼,有效解决了高锌物料在传统底吹熔炼中炉渣流动性差、锌回收率低、原料适应性差的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a high-zinc material bottom blowing smelting process and relates to the technical field of smelting.The process of the application effectively solves the problems of poor slag fluidity, low zinc recovery rate and poor raw material adaptability of high-zinc material in traditional bottom blowing smelting by adjusting and controlling the calcium-silicon ratio (CaO / SiO2 mass ratio) and the iron-silicon ratio (FeO / SiO2 mass ratio) of the furnace charge and cooperating with oxygen-rich bottom blowing intensified smelting. In the complex high-zinc bottom blowing smelting industrial experiment, the method of the application can increase the upper limit of the tolerance of the furnace body to the zinc grade of the raw material from 6wt% of the traditional process to 11wt%, so that the smelting enterprise can use a large amount of low-grade high-zinc lead-containing material, significantly reduce the cost and energy consumption, and does not need to make major equipment modification to the existing bottom blowing smelting production line, and is strong in economy and generalization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of smelting technology, and in particular to a bottom-blowing smelting process for high-zinc materials. Background Technology

[0002] Lead is an important non-ferrous metal material, widely used in petrochemicals, batteries, metallurgy, and nuclear industries due to its advantages such as low melting point, high corrosion resistance, poor penetration by X-rays and gamma rays, and good plasticity. my country is the world's largest producer and consumer of refined lead. However, with the development of the lead smelting industry and the depletion of mineral resources, high-grade lead ore is becoming increasingly scarce and difficult to develop and utilize. For small and medium-sized lead smelting enterprises, the only option is to seek smelting methods that handle complex high-zinc lead-containing materials.

[0003] Bottom-blown smelting is one of the mainstream lead smelting processes. Its core feature is the injection of oxygen-enriched gas from the bottom of the furnace, triggering a vigorous oxidation reaction, enhancing the oxidative decomposition of sulfide minerals, and reducing the need for carbonaceous fuels. However, traditional bottom-blown smelting processes have the following prominent problems when handling high-zinc materials: 1. Poor raw material adaptability: Traditional bottom-blown smelting processes have stringent requirements for the zinc grade in the feed material, generally requiring strict control below 6 wt%. When the zinc grade in the raw material exceeds 6 wt%, the furnace conditions deteriorate significantly, making normal production impossible. 2. Poor slag fluidity and high lead content in the slag. During the smelting of high-zinc materials, improper configuration of the calcium-silicon ratio (CaO / SiO2 mass ratio) and iron-silicon ratio (FeO / SiO2 mass ratio) in the furnace charge leads to a significant increase in slag viscosity. This results in slow ZnO diffusion within the slag, causing localized saturation precipitation and creating a vicious cycle of "high slag viscosity, slow ZnO diffusion, localized saturation precipitation, and further increase in slag viscosity." After cooling, the high-zinc slag has a porous and rough cross-section, with Zn, Si, and Fe elements highly overlapping in microscopic distribution, resulting in severely insufficient ZnO absorption capacity. Simultaneously, poor slag fluidity leads to incomplete slag-lead separation, with lead content exceeding 49% in the slag, causing lead loss. 3. High dust rate, low direct zinc recovery rate, and high energy consumption occur during the smelting of high-zinc materials. ZnO rapidly becomes supersaturated in the slag, and a large amount of undissolved ZnO powder is carried into the dust by the rising airflow, leading to an increased dust rate and a decreased direct zinc recovery rate. The flue gas contains a large amount of harmful substances such as As2O3 and Sb2O3, increasing the environmental pressure on subsequent flue gas treatment. 4. Low production efficiency, short furnace life, high slag viscosity, and difficulty in slag removal extend the single furnace operation cycle; the furnace charge is prone to caking on the furnace wall, aggravating furnace erosion and shortening the furnace life.

[0004] Therefore, there is an urgent need to develop a bottom-blown smelting process that can adapt to high-zinc materials, has a high zinc recovery rate, a low lead content in slag, and good slag fluidity. Summary of the Invention

[0005] In view of this, the present invention proposes a bottom-blowing smelting process for high-zinc materials to solve the above problems. The technical solution of the present invention is implemented as follows: A bottom-blown smelting process for high-zinc materials includes the following steps: S1. Ingredients: Mix and grind the high-zinc material, quartz sand, limestone and coke to obtain a mixture. The zinc content in the high-zinc material is 6wt%-11wt%, and the calcium-silicon ratio (CaO / SiO2 mass ratio) of the mixture is 0.38-0.44:1, and the iron-silicon ratio (FeO / SiO2 mass ratio) is 1.40-1.70:1. S2. Preheating feeding: Preheat the bottom blowing furnace to 750-850℃, and add the mixture into the bottom blowing furnace; S3, Bottom-blown smelting: Oxygen and nitrogen are injected from the bottom of the bottom-blown furnace to carry out two-stage smelting; S4. Separation and discharge: Slag, crude lead and dust-containing flue gas are discharged separately. The dust-containing flue gas is heated by the waste heat boiler and the dust is collected by the dust collection system. The sulfur-containing flue gas is sent to the acid production section.

[0006] Furthermore, in step S1, the zinc content in the high-zinc material is 6wt%-8wt%, and the calcium-silicon ratio (CaO / SiO2 mass ratio) of the mixture is controlled to be 0.40-0.44:1, and the iron-silicon ratio (FeO / SiO2 mass ratio) is controlled to be 1.55-1.70:1.

[0007] Furthermore, in step S1, the zinc content in the high-zinc material is 8wt%-11wt%, and the calcium-silicon ratio (CaO / SiO2 mass ratio) of the mixture is controlled to be 0.38-0.40:1, and the iron-silicon ratio (FeO / SiO2 mass ratio) is controlled to be 1.40-1.55:1.

[0008] The calcium-to-silicon ratio (CaO / SiO2 mass ratio) is a key parameter determining the acidity, alkalinity, and viscosity of slag. Traditional bottom-blown smelting employs a high calcium-to-silicon ratio (CaO / SiO2 mass ratio 0.5-0.7:1) alkaline slag to absorb the acidic SiO2 produced by the oxidation of sulfide ores and maintain slag fluidity by forming low-melting-point calcium-iron silicates. However, ZnO is an amphoteric oxide. In alkaline slag, ZnO exhibits weak acidity, reacting with free CaO in the slag to form high-melting-point calcium zincate microcrystals. In acidic slag, ZnO exhibits weak alkalinity, with ZnO... 2+ The ZnO forms a form that enters the silicate network structure. In traditional alkaline slag, the saturation solubility of ZnO is extremely low. When the zinc content of the raw material exceeds 6 wt%, the ZnO in the slag becomes rapidly supersaturated and precipitates out in large quantities in the form of free ZnO microcrystals or calcium zincate microcrystals. The dispersed solid particles cause the apparent viscosity of the slag to increase exponentially.

[0009] The iron-silicon ratio (FeO / SiO2 mass ratio) affects the melting point and structural stability of slag. Under the conditions of a high iron-silicon ratio (FeO / SiO2 mass ratio > 1.7:1) in traditional bottom-blown smelting processes, a large amount of high-melting-point fir olivine phase is generated in the slag, increasing the slag liquidus temperature. At temperatures of 1010-1020℃, the slag exists in a state where fir olivine solid particles and liquid phases coexist, making slag removal extremely difficult.

[0010] Simply increasing the temperature can reduce the viscosity of the liquid phase, but it cannot eliminate the solid particles precipitated by ZnO supersaturation, nor can it dissolve the already formed fritillary phase.

[0011] This invention adjusts the calcium-silicon ratio (CaO / SiO2 mass ratio) to 0.38-0.44:1 by reducing the amount of limestone and increasing the amount of quartz sand in the material, thereby changing the slag from alkaline to weakly acidic. After increasing the content of SiO2 network formations, the silicon-oxygen tetrahedra [SiO4] in the slag... 4- The increased degree of polymerization leads to a more open glass network structure, which in turn provides Zn with a more open environment. 2+ It provides a large number of non-bridging oxygen coordination sites. ZnO in acidic slag exhibits weak basicity, and Zn... 2+ By entering the silicate network as a network modifier, it is uniformly dispersed in a solid solution state rather than precipitating as an independent crystalline phase, fundamentally eliminating the problem of sudden changes in slag viscosity caused by supersaturated ZnO precipitates of solid particles.

[0012] If the calcium-silicon ratio (CaO / SiO2 mass ratio) of this invention is higher than 0.44:1, the slag viscosity remains too high, the improvement in slag fluidity is not significant, and the ZnO absorption capacity is insufficient. If the calcium-silicon ratio (CaO / SiO2 mass ratio) is lower than 0.38:1, the slag is too acidic, which will exacerbate the erosion of the furnace refractory material and reduce the furnace life. Therefore, a calcium-silicon ratio (CaO / SiO2 mass ratio) of 0.38-0.44:1 is the optimal range for balancing ZnO solubility, slag fluidity, and furnace life.

[0013] This invention adjusts the iron-silicon ratio (FeO / SiO2 mass ratio) to 1.4-1.7:1, effectively suppressing the formation of the high-melting-point fir olivine phase, lowering the slag melting point, and improving fluidity. If the iron-silicon ratio (FeO / SiO2 mass ratio) of this invention is higher than 1.7:1, the fir olivine phase content is too high, resulting in poor slag fluidity. If the iron-silicon ratio (FeO / SiO2 mass ratio) is lower than 1.4:1, the iron content is too low, weakening the fluxing effect of FeO as an important component of the slag and hindering the sedimentation and enrichment of lead droplets in the slag, thus increasing the lead content in the slag.

[0014] Furthermore, in step S3, the two-stage melting process specifically involves: heating to 950-1010℃ and controlling the oxygen-to-material ratio to be 80-100 Nm. 3 / t, react for 1-1.5h for a first-stage smelting, then continue heating to 1020-1080℃, controlling the oxygen-to-material ratio at 110-140Nm. 3 / t, react for 1.5-2h for two-stage smelting, to complete the separation of slag-lead-metal three phases.

[0015] Traditional processes operate with a single oxygen-to-material ratio throughout the entire process, which presents the following problems: if the oxygen-to-material ratio is low, the molten pool is not sufficiently stirred, and the slag-lead separation is incomplete; if the oxygen-to-material ratio is high, although it is advantageous during the separation period, in the early stages of smelting, strong stirring and high airflow will carry a large amount of undissolved ZnO powder into the flue dust, resulting in a decrease in the direct zinc recovery rate.

[0016] This invention employs a two-stage oxygen-to-material ratio: the first stage of melting uses a low oxygen-to-material ratio of 80-100 Nm. 3 The first stage operates at a lower temperature of 950-1020℃, with gentle stirring in the molten pool. This allows sufficient time for solid ZnO to dissolve and diffuse into the slag phase, rather than being mechanically carried into the flue gas by the gas flow, maximizing the solubility of ZnO in the slag. The second stage of smelting raises the temperature to 1020-1080℃, increasing the oxygen-to-material ratio to 110-140 Nm. 3 / t, by using strong stirring and high temperature to promote the separation of slag and lead two phases, the lead droplets are fully settled and enriched, thereby maximizing the direct recovery rate of zinc and reducing the lead content of slag.

[0017] Furthermore, the temperature of the first stage of melting is 980-1000℃, and the oxygen-to-material ratio is 85-95 Nm. 3 / t, the temperature of the second-stage smelting is 1045-1055℃, and the oxygen-to-material ratio is 115-135Nm. 3 / t: Furthermore, in step S3, the purity of the oxygen is ≥95% and the purity of the nitrogen is ≥99%.

[0018] Furthermore, in step S1, the high-zinc material includes a zinc content of 6wt%-11wt%, a lead content of 40wt%-45wt%, a copper content of 1.5wt%-2wt%, an FeO content of 8wt%-14wt%, a SiO2 content of 6wt%-12wt%, a CaO content of 3wt%-8wt%, and a sulfur content of 14wt%-18wt%.

[0019] Furthermore, in step S4, the temperature of the slag is 1000-1100℃; the lead content in the crude lead is ≤44%; and the temperature of the dust-laden flue gas is 950-1050℃.

[0020] Furthermore, in step S3, the oxygen quantity of a single oxygen lance in the bottom-blown furnace is ≤1200 Nm³. 3 / h, single-unit nitrogen flow rate ≤300 Nm 3 / h.

[0021] Compared with the prior art, the beneficial effects of the present invention are: 1. The process of the present invention effectively solves the problems of poor slag fluidity, low zinc recovery rate and poor raw material adaptability in traditional bottom blowing smelting of high zinc materials by adjusting the calcium-silicon ratio (CaO / SiO2 mass ratio) and iron-silicon ratio (FeO / SiO2 mass ratio) of the furnace charge and combining it with oxygen-enriched bottom blowing intensified smelting.

[0022] 2. This invention improves the saturated solubility of ZnO in acidic slag by adjusting the calcium-silicon ratio (CaO / SiO2 mass ratio) to 0.38-0.44:1 and utilizing the chemical properties of ZnO as a network modifier in acidic slag, thereby fundamentally solving the problem of sudden changes in slag viscosity caused by ZnO solid phase precipitation.

[0023] 3. This invention adjusts the iron-silicon ratio (FeO / SiO2 mass ratio) to 1.4-1.7:1, suppressing the large-scale formation of high-melting-point ferroalloy phase, and reconstructing the main phase of the slag into a low-melting-point ferroalloy-calcium feldspar eutectic system, achieving full liquid-phase operation within the operating temperature range. The slag viscosity is reduced, and the cross-section of the slag after cooling is smooth and flat with a dense microstructure. ZnO is uniformly distributed in the silicate glass phase in a solid solution state.

[0024] 4. This invention divides bottom-blown smelting into two stages: "zinc-slag intermelting period" and "three-phase separation period". Through differentiated control of the oxygen-material ratio in two stages, the slag dissolution efficiency of ZnO and the sedimentation and separation efficiency of lead droplets are maximized, achieving a zinc recovery rate of over 94% and a lead content in slag of less than 44%. This realizes the efficient enrichment and resource recovery of valuable metals in complex high-zinc materials.

[0025] 5. In complex high-zinc bottom-blown smelting industrial experiments, the method of this invention can increase the furnace body's tolerance limit to the zinc grade of raw materials from 6wt% in the traditional process to 11wt%, enabling smelting enterprises to use large quantities of low-grade high-zinc lead-containing materials, significantly reducing costs and energy consumption, without requiring major equipment modifications to existing bottom-blown smelting production lines, and has strong economic efficiency and scalability. Attached Figure Description

[0026] Figure 1 This is a physical image of the bottom-blown melting furnace of the present invention. Detailed Implementation

[0027] To better understand the technical content of this invention, specific embodiments are provided below to further illustrate the invention.

[0028] Unless otherwise specified, the experimental methods used in the embodiments of this invention are all conventional methods.

[0029] Unless otherwise specified, all materials and reagents used in the embodiments of this invention are commercially available.

[0030] The embodiments of the present invention use the bottom-blown smelting furnace of Hunan Huaxin Rare Precious Metals Technology Co., Ltd. as the experimental equipment. The bottom-blown furnace is configured with 3 surface feed ports and 6 oxygen lances. The oxygen is industrial oxygen (O2≥95%) and the nitrogen is industrial nitrogen (N2≥99%).

[0031] The high-zinc material composition of this invention is as follows: Pb 40wt%-45wt%, Zn 6wt%-11wt%, Cu 1.5wt%-2wt%, FeO 8wt%-14wt%, SiO2 6wt%-12wt%, CaO 3wt%-8wt%, and S 14wt%-18wt%. Material specifications: 80% of the material is 3-15mm, with a maximum size not exceeding 15mm. Its strength should be such that it does not break after being dropped from a height of 1 meter once.

[0032] The operating conditions for the bottom-blown smelting process of this invention are shown in the table below:

[0033] Example 1 The high-zinc material (100% by mass) fed into the furnace in this embodiment is as follows: Zn 8.0wt%, Pb 42.3wt%, Cu 1.8wt%, FeO 11.2wt%, SiO2 8.5wt%, CaO 5.1wt%, S 16.3wt%, with the balance being H2O; The bottom-blown smelting process for high-zinc materials includes the following steps: S1. Ingredients: Mix high-zinc materials, quartz sand, limestone and coke to make the calcium-silicon ratio (CaO / SiO2 mass ratio) of the mixture system 0.40:1 and the iron-silicon ratio (FeO / SiO2 mass ratio) 1.55:1, and grind and mix them evenly. S2. Preheating feed: Check the airtightness of the bottom blowing furnace, preheat the bottom blowing furnace to 800°C, and add the mixed material system into the bottom blowing furnace; S3. Bottom-blown smelting: Oxygen and nitrogen are injected from the bottom of the bottom-blown furnace, and the temperature is raised to 990℃, with the oxygen-to-material ratio controlled at 90Nm. 3 / t, react for 1 hour for a first-stage smelting, then continue heating to 1050℃, controlling the oxygen-to-material ratio at 120 Nm. 3 / t, react for 2 hours to carry out two-stage smelting, and complete the separation of slag-lead-metal three phases; S4. Separation and discharge: The slag is discharged from the furnace body, the lead liquid is discharged from the lead outlet to obtain crude lead, the dust-containing flue gas is fed into the dust collection system after heat recovery by the waste heat boiler, and the sulfur-containing flue gas is sent to the acid production section.

[0034] Tests showed that the zinc recovery rate was 97.7% and the lead content in the slag was 40.5%.

[0035] Example 2 The high-zinc material (100% by mass) fed into the furnace in this embodiment is as follows: Zn 10.5wt%, Pb 44.5wt%, Cu 1.7wt%, FeO 9.1wt%, SiO2 7.2wt%, CaO 3.8wt%, S 15.7wt%, with the balance being H2O. The bottom-blown smelting process for high-zinc materials includes the following steps: S1. Ingredients: Mix high-zinc materials, quartz sand, limestone and coke to make the calcium-silicon ratio (CaO / SiO2 mass ratio) of the mixture system 0.38:1 and the iron-silicon ratio (FeO / SiO2 mass ratio) 1.40:1, and grind and mix them evenly. S2. Preheating feed: Check the airtightness of the bottom blowing furnace, preheat the bottom blowing furnace to 850°C, and add the mixed material system into the bottom blowing furnace; S3. Bottom-blown smelting: Oxygen and nitrogen are injected from the bottom of the bottom-blown furnace, and the temperature is raised to 1000℃, with the oxygen-to-material ratio controlled at 95Nm. 3 / t, react for 1.5h for a first-stage smelting, then continue heating to 1055℃, controlling the oxygen-to-material ratio at 135 Nm. 3 / t, react for 2 hours to carry out two-stage smelting, and complete the separation of slag-lead-metal three phases; S4. Separation and discharge: The slag is discharged from the furnace body, the lead liquid is discharged from the lead outlet to obtain crude lead, the dust-containing flue gas is fed into the dust collection system after heat recovery by the waste heat boiler, and the sulfur-containing flue gas is sent to the acid production section.

[0036] Tests showed that the zinc recovery rate was 97.5% and the lead content in the slag was 41.4%.

[0037] Example 3 The high-zinc material (100% by mass) fed into the furnace in this embodiment is: Zn 6.2wt%, Pb 41.0wt%, Cu 2.0wt%, FeO 14.1wt%, SiO2 11.3wt%, CaO 4.1wt%, S 14.6wt%, with the balance being H2O; The bottom-blown smelting process for high-zinc materials includes the following steps: S1. Ingredients: Mix high-zinc materials, quartz sand, limestone and coke to make the calcium-silicon ratio (CaO / SiO2 mass ratio) of the mixture system 0.44:1 and the iron-silicon ratio (FeO / SiO2 mass ratio) 1.70:1, and grind and mix evenly. S2. Preheating feed: Check the airtightness of the bottom blowing furnace, preheat the bottom blowing furnace to 750°C, and add the mixed material system into the bottom blowing furnace; S3. Bottom-blown smelting: Oxygen and nitrogen are injected from the bottom of the bottom-blown furnace, the temperature is raised to 980℃, and the oxygen-to-material ratio is controlled at 85Nm. 3 / t, react for 1 hour for a first-stage smelting, then continue heating to 1045℃, controlling the oxygen-to-material ratio at 115 Nm. 3 / t, react for 1.5h to carry out two-stage smelting, and complete the separation of slag-lead-metal three phases; S4. Separation and discharge: The slag is discharged from the furnace body, the lead liquid is discharged from the lead outlet to obtain crude lead, the dust-containing flue gas is fed into the dust collection system after heat recovery by the waste heat boiler, and the sulfur-containing flue gas is sent to the acid production section.

[0038] Tests showed that the zinc recovery rate was 97.9% and the lead content in the slag was 40.7%.

[0039] Example 4 The high-zinc material (100% by mass) fed into the furnace in this embodiment is as follows: Zn 7.3wt%, Pb 42.3wt%, Cu 1.6wt%, FeO 12.0wt%, SiO2 10.1wt%, CaO 6.1wt%, S 15.1wt%, with the balance being H2O. The bottom-blown smelting process for high-zinc materials includes the following steps: S1. Ingredients: Mix high-zinc materials, quartz sand, limestone and coke to make the calcium-silicon ratio (CaO / SiO2 mass ratio) of the mixture system 0.43:1 and the iron-silicon ratio (FeO / SiO2 mass ratio) 1.65:1, and grind and mix evenly. S2. Preheating feed: Check the airtightness of the bottom blowing furnace, preheat the bottom blowing furnace to 810℃, and add the mixed material system into the bottom blowing furnace; S3. Bottom-blown smelting: Oxygen and nitrogen are injected from the bottom of the bottom-blown furnace, the temperature is raised to 980℃, and the oxygen-to-material ratio is controlled at 80Nm. 3 / t, react for 1 hour for a first-stage smelting, then continue heating to 1020℃, controlling the oxygen-to-material ratio at 110 Nm. 3 / t, react for 1.5h to carry out two-stage smelting, and complete the separation of slag-lead-metal three phases; S4. Separation and discharge: The slag is discharged from the furnace body, the lead liquid is discharged from the lead outlet to obtain crude lead, the dust-containing flue gas is fed into the dust collection system after heat recovery by the waste heat boiler, and the sulfur-containing flue gas is sent to the acid production section.

[0040] Tests showed that the zinc recovery rate was 95.2% and the lead content in the slag was 42.6%.

[0041] Example 5 The high-zinc material (100% by mass) fed into the furnace in this embodiment is: Zn 9.5wt%, Pb 43.6wt%, Cu 1.9wt%, FeO 9.2wt%, SiO2 7.5wt%, CaO 4.3wt%, S 16.5wt%, with the balance being H2O; The bottom-blown smelting process for high-zinc materials includes the following steps: S1. Ingredients: Mix high-zinc materials, quartz sand, limestone and coke to make the calcium-silicon ratio (CaO / SiO2 mass ratio) of the mixture system 0.39:1 and the iron-silicon ratio (FeO / SiO2 mass ratio) 1.45:1, and grind and mix evenly. S2. Preheating feed: Check the airtightness of the bottom blowing furnace, preheat the bottom blowing furnace to 770°C, and add the mixed material system into the bottom blowing furnace; S3. Bottom-blown smelting: Oxygen and nitrogen are injected from the bottom of the bottom-blown furnace, and the temperature is raised to 1010℃, with the oxygen-to-material ratio controlled at 100Nm. 3 / t, react for 1.5h for a first-stage smelting, then continue heating to 1080℃, controlling the oxygen-to-material ratio at 140 Nm. 3 / t, react for 2 hours to carry out two-stage smelting, and complete the separation of slag-lead-metal three phases; S4. Separation and discharge: The slag is discharged from the furnace body, the lead liquid is discharged from the lead outlet to obtain crude lead, the dust-containing flue gas is fed into the dust collection system after heat recovery by the waste heat boiler, and the sulfur-containing flue gas is sent to the acid production section.

[0042] Tests showed that the zinc recovery rate was 94.7% and the lead content in the slag was 43.2%.

[0043] Comparative Example 1 The difference between this comparative example and Example 1 is that, according to conventional parameters, the calcium-silicon ratio (CaO / SiO2 mass ratio) in step S1 is adjusted to 0.52:1 and the iron-silicon ratio (FeO / SiO2 mass ratio) is adjusted to 1.85:1, while the rest is the same as in Example 1.

[0044] Tests showed that the zinc recovery rate was 84.2% and the lead content in the slag was 49.1%.

[0045] Comparative Example 2 The difference between this comparative example and Example 1 is that the calcium-silicon ratio (CaO / SiO2 mass ratio) in step S1 remains unchanged at 0.40:1, and the iron-silicon ratio (FeO / SiO2 mass ratio) is adjusted to 1.85:1. The rest is the same as in Example 1.

[0046] Tests showed that the zinc recovery rate was 86.1% and the lead content in the slag was 47.8%.

[0047] Comparative Example 3 The difference between this comparative example and Example 1 is that the calcium-silicon ratio (CaO / SiO2 mass ratio) in step S1 is adjusted to 0.52:1, the iron-silicon ratio (FeO / SiO2 mass ratio) remains unchanged at 1.55:1, and the rest is the same as in Example 1.

[0048] Tests showed that the zinc recovery rate was 86.4% and the lead content in the slag was 48.1%.

[0049] Comparative Example 4 The difference between this comparative example and Example 1 is that in step S3, the temperature of the first stage of melting is adjusted to 920°C and the temperature of the second stage of melting is adjusted to 1010°C. The rest is the same as in Example 1.

[0050] Tests showed that the zinc recovery rate was 89.2% and the lead content in the slag was 46.8%.

[0051] Comparative Example 5 The difference between this comparative example and Example 1 is that, in step S3, the two-stage melting is not performed; that is, oxygen and nitrogen are injected into the bottom of the bottom-blown furnace, the temperature is raised to 1050°C, and the oxygen-to-material ratio is controlled at 135 Nm. 3 / t, reaction time 2h, other procedures are the same as in Example 1.

[0052] Tests showed that the zinc recovery rate was 91.2% and the lead content in the slag was 45.2%.

[0053] Test case The effects were compared and tested according to the processes of Examples 1-5 and Comparative Examples 1-5. The test items included: zinc recovery rate, lead content in slag, slag fluidity, and energy consumption change rate (relative to Example 1).

[0054] The results are shown in Table 1.

[0055] Table 1

[0056] As shown in Table 1, the processes in Examples 1-5 of this invention, by adjusting the calcium-silicon ratio (CaO / SiO2 mass ratio) and iron-silicon ratio (FeO / SiO2 mass ratio) of the furnace charge, combined with oxygen-enriched bottom blowing for enhanced smelting, effectively solve the problems of poor slag fluidity, low zinc recovery rate, and poor raw material adaptability in traditional bottom blowing smelting of high-zinc materials. This achieves a zinc recovery rate of over 94% and a lead content in the slag of less than 44%, realizing the efficient enrichment and resource recovery of valuable metals in complex high-zinc materials. Comparative Examples 2-5 show that the absence of any step in the calcium-silicon ratio (CaO / SiO2 mass ratio), iron-silicon ratio (FeO / SiO2 mass ratio), temperature, or segmented operation of this invention results in varying degrees of reduction in process effectiveness.

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A bottom-blown smelting process for high-zinc materials, characterized in that, Includes the following steps: S1. Ingredients: Mix and grind the high-zinc material, quartz sand, limestone and coke to obtain a mixture. The zinc content in the high-zinc material is 6wt%-11wt%, and the mass ratio of CaO / SiO2 in the mixture is 0.38-0.44:1, and the mass ratio of FeO / SiO2 is 1.40-1.70:

1. S2. Preheating feeding: Preheat the bottom blowing furnace to 750-850℃, and add the mixture into the bottom blowing furnace; S3, Bottom-blown smelting: Oxygen and nitrogen are injected from the bottom of the bottom-blown furnace to carry out two-stage smelting; S4. Separation and discharge: Slag, crude lead and dust-containing flue gas are discharged separately. The dust-containing flue gas is heated by the waste heat boiler and the dust is collected by the dust collection system. The sulfur-containing flue gas is sent to the acid production section.

2. The bottom-blown smelting process for high-zinc materials as described in claim 1, characterized in that, In step S1, the zinc content in the high-zinc material is 6wt%-8wt%, and the mass ratio of CaO / SiO2 in the mixture is controlled to be 0.40-0.44:1, and the mass ratio of FeO / SiO2 is controlled to be 1.55-1.70:

1.

3. The bottom-blown smelting process for high-zinc materials as described in claim 1, characterized in that, In step S1, the zinc content in the high-zinc material is 8wt%-11wt%, and the mass ratio of CaO / SiO2 in the mixture is controlled to be 0.38-0.40:1, and the mass ratio of FeO / SiO2 is controlled to be 1.40-1.55:

1.

4. The bottom-blown smelting process for high-zinc materials as described in claim 1, characterized in that, In step S3, the two-stage melting process specifically involves heating to 950-1010℃ and controlling the oxygen-to-material ratio to 80-100 Nm. 3 / t, react for 1-1.5h for a first-stage smelting, then continue heating to 1020-1080℃, controlling the oxygen-to-material ratio at 110-140 Nm. 3 / t, react for 1.5-2h for two-stage smelting, to complete the separation of slag-lead-metal three phases.

5. The bottom-blown smelting process for high-zinc materials as described in claim 4, characterized in that, The melting temperature of the first stage is 980-1000℃, and the oxygen-to-material ratio is 85-95 Nm. 3 / t, the temperature of the second-stage smelting is 1045-1055℃, and the oxygen-to-material ratio is 115-135Nm. 3 / t.

6. The bottom-blown smelting process for high-zinc materials as described in claim 1, characterized in that, In step S3, the purity of the oxygen is ≥95% and the purity of the nitrogen is ≥99%.

7. The bottom-blown smelting process for high-zinc materials as described in claim 1, characterized in that, In step S1, the high-zinc material includes zinc content of 6wt%-11wt%, lead content of 40wt%-45wt%, copper content of 1.5wt%-2wt%, FeO content of 8wt%-14wt%, SiO2 content of 6wt%-12wt%, CaO content of 3wt%-8wt%, and sulfur content of 14wt%-18wt%.

8. The bottom-blown smelting process for high-zinc materials as described in claim 1, characterized in that, In step S4, the temperature of the slag is 1000-1100℃; the lead content in the crude lead is ≤44%; and the temperature of the dust-laden flue gas is 950-1050℃.

9. The bottom-blown smelting process for high-zinc materials as described in claim 1, characterized in that, In step S3, the oxygen quantity of a single oxygen lance in the bottom-blown furnace is ≤1200 Nm³. 3 / h, single-unit nitrogen flow rate ≤300 Nm 3 / h.